Evaluation of Potential Fungal Species for the in situ Simultaneous Saccharification and Fermentation (SSF) of Cellulosic Material - Micky A, Vincent; Anthony L, Pometto III; Johannes, Leeuwen (MyJurnal, 2011)
Three fungal species were evaluated for their abilities to saccharify pure cellulose. The three species chosen represented three major wood-rot molds; brown rot (Gloeophyllum trabeum), white rot (Phanerochaete chrysosporium) and soft rot (Trichoderma reesei). After solid state fermentation of the fungi on the filter paper for four days, the saccharified cellulose was then fermented to ethanol by using Saccharomyces cerevisiae. The efficiency of the fungal species in saccharifying the filter paper was compared against a low dose (25 FPU/g cellulose) of a commercial cellulase. Total sugar, cellobiose and glucose were monitored during the fermentation period, along with ethanol, acetic acid and lactic acid. Results indicated that the most efficient fungal species in saccharifying the filter paper was T. reesei with 5.13 g/100 g filter paper of ethanol being produced at days 5, followed by P. chrysosporium at 1.79 g/100 g filter paper. No ethanol was detected for the filter paper treated with G. trabeum throughout the five day fermentation stage. Acetic acid was only produced in the sample treated with T. reesei and the commercial enzyme, with concentration 0.95 and 2.57 g/100 g filter paper, respectively at day 5. Lactic acid production was not detected for all the fungal treated filter paper after day 5. Our study indicated that there is potential in utilizing in situ enzymatic saccharification of biomass by using T. reesei and P. chrysosporium that may lead to an economical simultaneous saccharification and fermentation process for the production of fuel ethanol.